'Insecticidal efficacy of a hormonal analogue on the post-embryonic development of a flesh fly, Sarcophaga ruficornis (Diptera: Sarcophagidae)'. Issue 3 (2nd October 2022) - Singh, K. P.; Maddheshiya, Rahul
ABSTRACT: Sarcophaga ruficornis (Fabricius 1794) causes myiasis in humans and other vertebrates. It has a wide distribution across tropical countries. In the present investigation, the effect of a juvenile hormone analogue, fenoxycarb has been observed on the last instar larvae of S. ruficornis . The last instar larvae (0, 1 and 2-days old) of this dipteran fly were treated topically with sub-lethal doses (10, 20, 40, 60 and 80 µg/µl/larva) of fenoxycarb. Several effects were observed such as mortality, abnormal pupariation, reduction pupariation, adult emergence and eclosion failure. Pupal-adult intermediates and the emergence of abnormal adults were also observed. Log Inhibitory concentration (LogIC50 ) causing inhibition of normal pupariation was 1.68, 1.8 and 1.681 µg/µl in 0, 1 and 2-days of larval treatments respectively. Whereas LogIC50 values inhibiting the adult emergence were 1.297, 1.359 and 1.482 µg/µl in 0, 1, and 2-days of larval treatments respectively. Results manifest the potency of fenoxycarb in the control of larval-adult transformation in S. ruficornis .